(untitled) (Academia Science Repository, 2023)
The article discusses the features of the process of formation of professional competencies of students of a pedagogical university. Particular attention is paid to the analysis of the use of theoretical and methodological approaches that allow studying the structure of preparation for professional activity from the standpoint of increasing its effectiveness: systemic, activity-praxeological, competence-based, as well as the development of a pedagogical system for the formation of students’ professional competencies